Consultation hours: The effectiveness of face-to-face consultation outside the classroom / Norlaili Harun and Raihanah Mohamad - Harun, Norlaili; Mohamad, Raihanah (2006)
The learning process involves tutors/lecturers and students at any level of education. The communication between the two groups occurs formally in the classroom where all the subjects are taught. Informally the communication will continue outside of the classroom when the students want to ask or consult the tutors/lecturers. Consultation happens during consultation time or outside of the time set. This study investigates how far face-to-face consultation, which is out-of-class (OOC) communication, is effective to the students. The respondents were full-time students of more than two-semester experience as students at UiTM Jengka. Pahang. The findings of the study suggested that consultation was important to them and it also helped in their performance. Moreover, consultation offered better understanding and relationship among the students and tutors/lecturers. The study also found that the different time-table and schedule between the two groups discouraged some of the students to go for consultation.